An assessment of the progress made in the implementation of the regional framework for cholera prevention and control in the WHO African region - Miriam Nanyunja; Allan Mpairwe; Ibrahim Mamadu; Otim Patrick Cossy Ramadan; Mory Keïta; Tamayi Mlanda; Abdou Salam Gueye; Ebenezer Obi Daniel; Etien Luc Koua; Dick Chamla; Fiona Braka; Fred Kapaya; et al. (BMJ Global Health)
High-burden cholera outbreaks, spreading beyond the traditional cholera-endemic countries, have been reported since 2021 in the WHO African region. Member states in the region have committed to the global goal of cholera elimination by 2030. To track progress towards this goal, WHO-African countries adopted a regional cholera prevention and control framework in 2018. This study reports on 27 countries’ 5-year achievements in implementing the cholera regional framework for cholera prevention, and control. Data collected through a web-based self-assessment tool were analysed and visualised through Power BI. Data were provided by national teams of experts on cholera based on the milestones of the framework. Countries’ specific progress and regional progress were calculated. The overall regional progress was 53%, ranging from 19% in Mauritania to 76% in Ethiopia. Out of the 27 countries, 3 had made good progress while 14 had fair and 10 had insufficient progress. At the regional level, 4 milestones were on track, 7 were fair and 10 had insufficient progress. Cholera hot spot mapping had the highest score at 85%, while development of investment cases for cholera control scored the lowest at 14%. Although appreciable progress was noted in some milestones, the progress against critical milestones, including for water, sanitation and hygiene, that form the bedrock of cholera control, was insufficient. Effective implementation of the cholera prevention and control framework anchored on strong government commitment and ownership is essential to curb the current trend of cholera outbreaks and improve the likelihood of cholera elimination by 2030 in Africa.